Synthesis and Evaluation of Morpholinoethyl Ester Conjugate of N-acetylcysteine in Ovalbumin-induced Airway Hyperresponsiveness in Sprague Dawley Rats - V. Bhilare, Neha; S. Dhaneshwar, Suneela (Letters in Drug Design & Discovery, 2017)
N-acetylcysteine (NAC) exhibits diverse pharmacological effects due to the free radical scavenging ability of the reduced thiol. Extensive deacetylation in liver, high protein binding and poor permeability results in low bioavailability of NAC. These setbacks are also the contributing factors in failure to confirm the benefits of NAC in prevention of diseases involving oxidative stress. Present study was aimed at improving the bioavailability of NAC by conjugating it with morpholinoethanol into a morpholinoethyl ester conjugate (A-2). A-2 was synthesized by DCC coupling and the structure was confirmed by IR, 1H-NMR, 13C-NMR, elemental analysis and mass spectroscopy. This conjugate was screened in ovalbumin-induced airway hyperresponsiveness for various lung function parameters where it exhibited significant ameliorating effect; interestingly at half the equimolar dose of NAC. Thus, A-2 has the potential to be used as a substitute for NAC in conditions involving airway hyperresponsiveness and airway eosinophilia.
Keywords: N-acetylcysteine